OP0020 LESS IS MORE: ANA-LYSING THE IMPACT OF REPEATED ANTINUCLEAR ANTIBODY TESTING. (June 2019) - Yeo, Ai Li; Ong, Jason; Connelly, Kathryn; Le, Suong; Ptasznik, Ronnie; Ross, Jane; Morand, Eric F.; Leech, Michelle
Abstract : Background: Minimising unnecessary tests is a global health economic priority with multiple initiatives in place to avoid inappropriate healthcare utilisation(1) and harm. Anti-nuclear antibody (ANA) testing is frequently performed as a diagnostic test for autoimmune conditions, such as systemic lupus erythematosus (SLE) or as a screening test in patients with inflammatory or musculoskeletal symptoms. The value of serial testing in the monitoring of such conditions is unclear and false positive tests can lead to unnecessary further investigation and increased patient anxiety(2) Objectives: To evaluate the frequency of repeated ANA testing as a prelude to Electronic Medical Record (EMR) test alert design in an Australian healthcare network. The primary endpoint was calculation of the total cost associated with repeated testing and whether a longitudinal change in ANA resulted in any new ANA associated rheumatological diagnoses. Our secondary endpoint was the examination of baseline ANA testing behaviours. Methods: We retrospectively analysed data from a multi-centre tertiary health network in Melbourne, Australia across a 7-year period (19 March 2011 to 23 July 2018). ANA and other autoimmune test results were obtained from the hospital pathology system with a positive ANA cut off set at 1:160. Clinical information was sourced from clinical information systems on patients who had a change in ANA result from negative to positive on repeat testing. The associated cost of repeated ANA testing was calculated based on the baseline cost to the public system. Results: A total of 36, 715 ANA tests (excluding 980 cancelled same-day requests) were performed in 28, 840 patients. Of these, 14, 058 (38.3%) were positive with females accounting for 9, 265 (65.9%, p<0.001). The most frequent ANA patterns were homogenous (47.4%) and nucleolar (23.3%). ANA titres were as follows; 1:160 (41.4%), 1:320 (15.3%), 1:640 (13.1%) and 1:1280 (29.2%). 7, 875 (21.4%) of tests were repeat tests. Of these 511 (6.5%) results changed from negative to positive. The median time between a negative ANA result to the first positive result was 1.71 years (IQR 0.50-3.55). Clinical information was captured for a median duration of 1.24 years (IQR 0.50-2.07) following a positive ANA result. A change to positive ANA was associated with a new ANA-associated rheumatological diagnosis in only 5 cases (2 SLE, 1 scleroderma and 2 undifferentiated connective tissue disease) with a positive predictive value calculated at 0.01. When comparing patients who with a new diagnosis to those with no new diagnosis, there was no difference between ANA titre, pattern, duration to first positive ANA, ordering location or clinician, or age of first positive ANA test. The direct total cost for the government of all ANA testing was AUD903, 189, of which repeat testing contributed AUD193, 725. Conclusion: Repeat ANA testing after a negative result had limited utility in the diagnosis of ANA associated rheumatological conditions with a positive predictive value of only 0.01, and resulted in high cost. New technology and clinical alert systems may help reduce unnecessary testing with potential significant direct cost savings when extrapolated across the Australian healthcare system. References: [1] Levinson W, Kallewaard M, Bhatia RS, Wolfson D, Shortt S, Kerr EA. 'Choosing Wisely': a growing international campaign. BMJ Qual Saf. 2015;24(2):167-74. [2] Abeles AM, Abeles M. The clinical utility of a positive antinuclear antibody test result. The American journal of medicine. 2013;126(4):342-8. Disclosure of Interests: Ai Li Yeo: None declared, Jason Ong: None declared, Kathryn Connelly: None declared, Suong Le: None declared, Ronnie Ptasznik: None declared, Jane Ross: None declared, Eric F. Morand Grant/research support from: AstraZeneca, Bristol Myers Squibb, Janssen, Merck Serono, and UCB, Consultant for: AstraZeneca, Eli Lilly, Janssen, and Merck Serono, Speakers bureau: AstraZeneca, Michelle Leech: None declared